Developing Ti Jewelry Through Additive Manufacturing and Conversion Technologies - B. Paiva (2011)
Nowadays there are an enormous variety of titanium (Ti) jewelry artifacts. These products have a high specific strength, are corrosion resistant, promote a warm feeling to the human touch and are easily surface modified by temperature or anodization to acquire a sophisticated aesthetic colour. Ti is more durable than gold or platinum, has a lower price and is a fashion material due to the successful use in challengeable applications. This paper describes the importance of using additive manufacturing and conversion processes to develop innovative jewelry titanium artifacts. Combining 3D modelling, stereolithography, conversion technologies with silicone and low melting point metallic molds and precision casting in ceramic shells molds in controlled atmosphere, we were able to manufacture complex shapes with shiny thin sections, that after an adequate heat treatment exhibit a variety of attractive colors that are more difficult and expensive to obtain with existing technology for manufacturing jewelry products (metal forming and machining).